Does trade cause long-run development? Theory and evidence from countries behind the Suez channel - Michiel Gerritse (European Regional Science Association (ERSA), 2015)
Does trade improve institutions and contribute to long run growth? I develop a theory of trade, in which trade liberalization provides incentive to change institutions in two ways. On the one hand, trade leads to specialization according to comparative advantage, expanding the industries that do not rely on contracting institutions in less developed countries. The Heckscher-Ohlin-type effect lowers the demand for contract enforcement, as documented in earlier literature. On the other hand, if firms are imperfectly competitive, they have an interest in minimizing their marginal costs. As institutional frictions in the factor markets are costly, they raise output prices and cause losses of sales for imperfectly competitive firms. When the economy opens up, the sales-reducing effects of poor institutions are aggravated, because the effective market size increases. As a result, increased market acces through trade liberalization can increase the demand for contract. Thus, trade liberalization may also increase the demand for good institutions. That idea underlies much of the debates on globalization and 'aid for trade', and this is one of the first papers to provide an economic rationale. I exploit the 1967-1975 war-induced closing of the Suez channel as a quasi-natural experiment. The war between Israel and Egypt was not anticipated, let alone caused by countries on the Eastern coast of Africa. During the closing of the channel, countries in the east of Africa had substantially larger trade costs towards Europe than countries on the western coast, which led to significant declines in trade volume. When the Suez channel was closed, countries with increased trade costs specialized in industries that relied less on institutions (less fixed costs, less differentiated products, less contract-intensive inputs). The opening up of the Suez channel in 1975 caused the opposite effect. The trade cost shock is arguably exogenous and I use a dif-in-dif-in-dif (country - industry - trade cost) estimator to control for the effects of trade costs at the country and industry level. The increase in trade costs held exclusively for shipping, thus making access to information, capital or people a less likely explanation for the results. The results persist even though comparative advantage determines trade patterns - capital-intensive industries benefitted from increased trade costs to Europe. The results therefore suggest that trade liberalization does not deteriorate institutions in less developed countries.
Keywords: O19; F63; F43; C31; F11; N77; F12; O43; O11; 330; institutions and trade; dif-in-dif/quasi experiment; long-run development